The relationship between the characteristics of the transformational leader and the entrepreneur in South African SMEs - D. J. Visser; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 2005)
Transformational leadership, as found in large firms can be applied to entrepreneurial leaders in SMEs. Since significant transformation is being brought about in organisations by changes in technology, international competition and workforces which become more diverse, literature proposes that this type of leadership is becoming more important to organisations. Similarly, there is a need for a `new' style of leadership in South African SMEs, especially those enterprises which display the capacity and capability to enter and compete in world markets. Since the literature clearly indicates that transformational leadership is a behavioural process which can be learned, the purpose of this paper is twofold: firstly, to identify the profile elements of entrepreneurship and transformational leadership in SMEs which, if applied appropriately, will in all probability, lead to organisational innovation; and, secondly, to determine whether entrepreneurs in SMEs in the South African context possess characteristics that manifest them as transformational leaders. It is demonstrated that a significant and positive relationship exists between the characteristics of an entrepreneur and the characteristics of a transformational leader in South African SMEs.
Keywords: 650